Body Mass Index and HbA1c Are Associated with Renal and Hepatic Function - Yoga Mulia Pratama; Falah Faniyah; Imam Nafiyana Saputra (Saintika Medika, 2021)
Hypertension and diabetes may have implications for damage to other organs such as the kidneys and liver which are evaluated by serum creatinine and ALT, respectively. This study aims to delineate the association between body mass index and hbA1c with renal and hepatic function, respectively. This is a cross-sectional study involving 32 subjects. The research subjects consisted of diabetics and hypertension who were registered in the Muhammadiyah Primary Health Care, Kebanaran, Purwokerto. It was found that in diabetics, there were significant results between serum creatinine and HbA1c values (p <0.01, r = 0.855). Systolic blood pressure was correlated with body mass index (BMI) (p <0.01, r = 0.649). In patients with hypertension, serum creatinine was correlated with the length of time a person has hypertension (p <0.01, r = 0.475). Meanwhile, the ALT value was correlated with body mass index (p <0.05, r = 0.422) and waist circumference (p <0.001, r = 0.528). We found that a decreased HbA1c levels significantly reduces serum creatinine levels so it may also reduce kidney damage. A decrease in the value of BMI and waist circumference significantly reduces ALT enzyme levels which may have the potential for reducing liver damage.